RnBeads 2.0: comprehensive analysis of DNA methylation data - Müller, Fabian; Scherer, Michael; Assenov, Yassen; Lutsik, Pavlo; Walter, Jörn; Lengauer, Thomas; Bock, Christoph (Genome Biology, 2019)
DNA methylation is a widely investigated epigenetic mark with important roles in development and disease. High-throughput assays enable genome-scale DNA methylation analysis in large numbers of samples. Here, we describe a new version of our RnBeads software - an R/Bioconductor package that implements start-to-finish analysis workflows for Infinium microarrays and various types of bisulfite sequencing. RnBeads 2.0 ( https://rnbeads.org/ ) provides additional data types and analysis methods, new functionality for interpreting DNA methylation differences, improved usability with a novel graphical user interface, and better use of computational resources. We demonstrate RnBeads 2.0 in four re-runnable use cases focusing on cell differentiation and cancer.